Dialysis Initiation in Patients With Chronic Coronary Disease and Advanced Chronic Kidney Disease in ISCHEMIA-CKD - Briguori, C (2022)
Background In participants with concomitant chronic coronary disease and advanced chronic kidney disease (CKD), the effect of treatment strategies on the timing of dialysis initiation is not well characterized. Methods and Results In ISCHEMIA-CKD (International Study of Comparative Health Effectiveness With Medical and Invasive Approaches-Chronic Kidney Disease), 777 participants with advanced CKD and moderate or severe ischemia were randomized to either an initial invasive or conservative management strategy. Herein, we compare the proportion of randomized participants with non-dialysis-requiring CKD at baseline (n=362) who initiated dialysis and compare the time to dialysis initiation between invasive versus conservative management arms. Using multivariable Cox regression analysis, we also sought to identify the effect of invasive versus conservative chronic coronary disease management strategies on dialysis initiation. At a median follow-up of 23 months (25th-75th interquartile range, 14-32 months), dialysis was initiated in 18.9% of participants (36/190) in the invasive strategy and 16.9% of participants (29/172) in the conservative strategy (P=0.22). The median time to dialysis initiation was 6.0 months (interquartile range, 3.0-16.0 months) in the invasive group and 18.2 months (interquartile range, 12.2-25.0 months) in the conservative group (P=0.004), with no difference in procedural acute kidney injury rates between the groups (7.8% versus 5.4%; P=0.26). Baseline clinical factors associated with earlier dialysis initiation were lower baseline estimated glomerular filtration rate (hazard ratio [HR] associated with 5-unit decrease, 2.08 [95% CI, 1.72-2.56]; P<0.001), diabetes (HR, 2.30 [95% CI, 1.28-4.13]; P=0.005), hypertension (HR, 7.97 [95% CI, 1.09-58.21]; P=0.041), and Hispanic ethnicity (HR, 2.34 [95% CI, 1.22-4.47]; P=0.010). Conclusions In participants with non-dialysis-requiring CKD in ISCHEMIA-CKD, randomization to an invasive chronic coronary disease management strategy (relative to a conservative chronic coronary disease management strategy) is associated with an accelerated time to initiation of maintenance dialysis for kidney failure.